# 1.3. Consistency of MLE

$\newcommand{\argmin}{\mathop{\mathrm{argmin}}\limits}$ $\newcommand{\argmax}{\mathop{\mathrm{argmax}}\limits}$

The last example de Geer (2000) presents is the consistency of maximum likelihood estimates as the last example.1 Specifically, I would like to briefly prove Hellinger consistency of MLE provided that some form of law of large numbers holds.

The essential of this example is, if we have a uniform law of large numbers then we can prove consistency of MLE even in a nonparametric setting.

## (Pseudo) metrics for consistency

### Hellinger distance

Hellinger distance (or, Hellinger metric) is frequently used to show consistency of estimates. The metric $h$ is defined as a function of integrated squared difference of square roots of densities:

$h(p, q) := \left( \frac12 \int ( \sqrt p - \sqrt q )^2 d\mu \right)^{1/2},$

where $\mu$ is a measure dominating the distributions of $p$ and $q.$

### Kullback-Leibler divergence

Although it is not a metric2, the KL divergence $K(\cdot,\cdot)$ has been used extensively due to its relationship with metrics on a space of densities.

$K(p, q) := \int \log\frac{p(x)}{q(x)}p(x)d\mu(x),$

where $\mu$ is the dominating measure of the density $p.$ In other words, for a density indexed by $\theta,$

$K(p_{\theta_0}, p_\theta) = E_{\theta_0}\log\frac{p_{\theta_0}}{p_\theta}.$

The following fact shows that it suffices to show KL consistency in order to show Hellinger consistency.

$$h^2(p_{\theta_0}, p_\theta) \le \frac 1 2 K(p_{\theta_0}, p_\theta).$$

The famous inequality $$\log x \le x -1$$ is all we need for the proof.

Hence we will show that the ULLN is a sufficiency of KL consistency.

## KL consistency of the MLE

$X \sim p_{\theta_0},~ \theta_0 \in \Theta$

where $p_{\theta_0}$ is a Radon-Nikodym density with respect to a $\sigma$-finite measure $\mu.$ Here, $\Theta$ can be either finite or infinite. Let $(X_i)_ {i=1}^n$ be a random sample from $p_{\theta_0}.$ Then

$\hat\theta_n := \argmax_{\theta\in\Theta} \sum_{i=1}^n \log p_{\theta}(X_i)$

is the MLE of $\theta_0$.

By definition, the following inequality holds3.

\begin{aligned} \text{(1)}&\; \sum_{i=1}^n \log\frac{p_{\theta_0}(X_i)}{p_{\hat\theta_n}(X_i)} \le 0 \\ \text{(2)}&\; E_{\theta_0} \log\frac{p_{\theta_0}(X)}{p_\theta(X)} \ge 0,~ \forall\theta\in\Theta \end{aligned}

It is convenient to define

$g_\theta(\cdot)=\log\frac{p_{\theta_0}(\cdot)}{p_\theta(\cdot)},$

so that we can express $K(p_{\theta_0}, p_\theta) = Eg_\theta(X).$ It is clear by the strong law of large numbers that

$\left| \frac 1 n \sum_{i=1}^n g_{\theta}(X_i) - K(p_{\theta_0}, p_{\theta}) \right| \to 0 \text{ a.s.}$

Here, $\theta$ is fixed. Suppose the same result holds for a sequence $(\hat\theta_n)_ {n\in\mathbb N}.$ That is,

$\left| \frac 1 n \sum_{i=1}^n g_{\hat\theta_n}(X_i) - K(p_{\theta_0}, p_{\hat\theta_n}) \right| \to 0 \text{ a.s.} \tag{3}$

Using the inequality (1) coupled with this “uniform” strong law yields the result.

$$\left| \frac 1 n \sum_{i=1}^n g_{\hat\theta_n}(X_i) - K(p_{\theta_0}, p_{\hat\theta_n}) \right| \to 0 \text{ a.s.} \\ \implies K(p_{\theta_0}, p_{\hat\theta_n}) \to 0 \text{ a.s.}$$

\begin{aligned} 0 &\ge \frac1n\sum_{i=1}^n g_{\hat\theta_n}(X_i) \\ &= \frac1n\sum_{i=1}^n g_{\hat\theta_n}(X_i) - K(p_{\theta_0}, p_{\hat\theta_n}) + K(p_{\theta_0}, p_{\hat\theta_n}). \end{aligned} Therefore, \begin{aligned} K(p_{\theta_0}, p_{\hat\theta_n}) &\le \left| \frac 1 n \sum_{i=1}^n g_{\hat\theta_n}(X_i) - K(p_{\theta_0}, p_{\hat\theta_n}) \right| \\ &\to 0 \text{ a.s. as } n \to \infty. \end{aligned}

### Slower, but more obtainable rate

The ULLN (3) might not be easily obtainable, or might not even a fact in many cases. In this case, an extension of CLT can be used similarly as before.

$\frac 1 {\sqrt n} \sum_{i=1}^n \big( g_\theta(X_i) - K(p_{\theta_0}, p_\theta) \big) \overset d \to \mathcal{N}\left(0, \text{Var}(g_\theta(X)) \right)$

which gives the rate

$\left| \frac 1 n \sum_{i=1}^n g_{\theta}(X_i) - K(p_{\theta_0}, p_{\theta}) \right| =\mathcal{O}_P(n^{-1/2}).$

Suppose the result holds for a sequence $(\hat\theta_n)_ {n\in\mathbb N}$:

$\left| \frac 1 n \sum_{i=1}^n g_{\hat\theta_n}(X_i) - K(p_{\theta_0}, p_{\hat\theta_n}) \right| =\mathcal{O}_P(n^{-1/2}).$

Then by the same argument, we can obtain KL - thus Hellinger - consistency of the MLE with the rate $\mathcal{O}_P(n^{-1/2}).$

References

• van de Geer. 2000. Empirical Processes in M-estimation. Cambridge University Press.
• Theory of Statistics II (Fall, 2020) @ Seoul National University, Republic of Korea (instructor: Prof. Jaeyong Lee).

1. In fact, it is the second one but I switched the order to make things more clear.

2. For those who are interested, there is a metric derived from it

3. The left-hand side of the inequality (1) is sometimes referred to as the empirical KL divergence